Context is key: Understanding the regulation, functional control, and activities of the p53 tumour suppressor. (30th September 2020) - Moxley, Anne H.; Reisman, David
Abstract : The p53 tumour suppressor is considered one of the most critical genes in cancer biology. By upregulating apoptosis, cell cycle arrest, and DNA damage repair in normal cells, p53 prevents the propagation of cells with tumorigenic potential; therefore, mutations in p53 are associated with carcinogenic transformation and can be accompanied by the accumulation of a novel gain‐of‐function oncogenic protein, mutant p53. Although p53 is most often understood to utilize context‐dependent post‐translational modifications to achieve regulation of its many target genes, recent research has also sought to define other mechanisms of regulating p53 gene expression prior to translation and to understand how this alternative regulation of p53 may influence target gene expression and cellular outcome. This review attempts to summarize what is known about p53 regulation at the transcriptional, post‐transcriptional, and post‐translational levels while paying special attention to the ways in which context may influence p53 regulation and subsequent regulation of its target genes.